DAMPAK TATA RUANG WILAYAH TERHADAP AKTIVITAS KEWIRAUSAHAAN DAN PERTUMBUHAN USAHA PETERNAKAN AYAM BROILER DI PROVINSI JAMBI - Rufti Puji Astuti; Rachmad Pambudy; Burhanuddin Burhanuddin (Diponegoro University, 2016)
Spatial is one issue that is important in assessing the concept of entrepreneurship. Interest studied the problems of spatial and entrepreneurship is to create business growth, through the support of business locations atmosphere, leading to the creation of entrepreneurial activity. The purpose of this study to (1) identify the determining factors of the characteristics of the zone; (2) to analyze the influence of the characteristics of the zone of entrepreneurial activity; (3) Analyze the effects of entrepreneurial activity on the growth of broiler chicken farm. The research was conducted by survey method, conducted in three zones in Jambi province with a total sample of 140 farmers. The results showed (1) Characteristics of the zone formed by the spatial characteristics, enterprises and entrepreneurs. (2) Characteristics of significant zones of direct and positive effect on entrepreneurial activity (3) entrepreneurial activities significantly affect the growth of broiler chicken farm, both of which have a positive relationship. In other words, the growth of the business acquired, occur because of the encouragement of entrepreneurial activity increased farmers.